2017
DOI: 10.1371/journal.pone.0170371
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Cervical Cancer Screening Coverage: A Randomised, Community-Based Clinical Trial

Abstract: BackgroundOpportunistic cervical cancer screening can lead to suboptimal screening coverage. Coverage could be increased after a personalised invitation to the target population. We present a community randomized intervention study with three strategies aiming to increase screening coverage.MethodsThe CRICERVA study is a community-based clinical trial to improve coverage of population-based screening in the Cerdanyola SAP area in Barcelona.A total of 32,858 women residing in the study area, aged 30 to 70 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…As such, they can help to develop more effective screening interventions (Painter et al, 2008;Parsa et al, 2017 ). Indeed, while demographic factors that influence screening behavior can be taken into account but not modified (Acera et al, 2017) psychological factors that determine screening behavior can be addressed directly. As such, the use of theories about health behavior can inform the development of more effective strategies for encouraging women to participate in CCS.…”
Section: Health Behavior Theories and Their Applicationmentioning
confidence: 99%
“…As such, they can help to develop more effective screening interventions (Painter et al, 2008;Parsa et al, 2017 ). Indeed, while demographic factors that influence screening behavior can be taken into account but not modified (Acera et al, 2017) psychological factors that determine screening behavior can be addressed directly. As such, the use of theories about health behavior can inform the development of more effective strategies for encouraging women to participate in CCS.…”
Section: Health Behavior Theories and Their Applicationmentioning
confidence: 99%
“…Under opportunistic screening approaches, loss to follow-up is common. We have shown that inviting these women can quickly revert the situation [36]. The use of personal reminders increased significantly screening participation even if only an invitation letter with a scheduled visit was used [36,37].…”
Section: Plos Onementioning
confidence: 88%
“…We have shown that inviting these women can quickly revert the situation [ 36 ]. The use of personal reminders increased significantly screening participation even if only an invitation letter with a scheduled visit was used [ 36 , 37 ]. Generally, in organized programs, higher adherence to the screening programs is attained [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is seen from studies that several countries in the world are using various strategies like health education, personal invitation by phone calls, by letters, distributing pamphlets, removing screening fee etc., to increase attendance at cervical cancer camps. [16][17][18][19] The investigators have attempted to conduct cervical screening camps earlier. Past experience of the investigators and other studies done in India show low participation in such conducted camps.…”
Section: Discussionmentioning
confidence: 99%